CHANGES IN THE PARAMETERS OF BLOOD LIPIDS AND CYTOKINES IN PATIENTS WITH PRIMARY OSTEOARTHRITIS DURING TREATMENT WITH ARTHRA - E Yu Alexenko; A V Govorin (Научно-практическая ревматология, 2011)
Objective: to study the time course of changes in the cytokine profile, the parameters of lipid peroxidation (LPO), antioxidant defense, and lipid spectrum during Arthra therapy in patients with primary osteoarthritis (POA). Subjects and methods. The study was conducted in 26 POA patients (aged 39.5+5.4 years) with knee and hip joint lesions in the absence of synovitis. The efficiency of treatment was evaluated by pain intensity and WOMAC index. The levels of proinflammatory cytokines, lipids, LPO primary and intermediate products, and antioxidant defense were compared in patients with PAO prior to and 12 and 24 weeks after Arthra therapy. Results. Positive changes in articular manifestations were determined after 24 weeks of therapy, by using the WOMAC scale. The mean concentration of C-reactive protein (CRP) was halved in the patients 24 weeks following the start of Arthra therapy. The blood levels of IL-1β, IL-6, IL-18, TNF-α decreased just after 12 weeks of therapy as compared to the baseline level and continued to decline by the end of the therapy. There were reductions in LPO primary and intermediate products in serum and red blood cells. There was activation of antiradical protection (increases in serum and red blood cell catalase activities and serum antioxidant activity and a decrease in the number of hemolyzed red blood cells). After a course of therapy, there were reduced blood concentrations of total cholesterol and low-density lipoprotein (LDL) cholesterol in patients with POA. Conclusion. The POA patients treated with Arthra displayed improvements in LPO profile and antioxidant defense and lower blood concentrations of cholesterol and LDL cholesterol along with a decline in the levels of the blood cytokines IL-1β, IL-6, IL-18, TNF-α, and CRP.